Self-Nanoemulsifying Drug Delivery System to Enhance Solubility and Dissolution of Lipophilic Drug Repaglinide - Raghuveer, Pathuri (Asian Journal of Pharmaceutics (AJP), 2020)
Introduction: Self-nanoemulsifying drug delivery systems (SNEDDSs) are isotropic mixture of oil, surfactant, cosurfactant, and drug that form fine oil in water emulsion when get contact with water on mild agitations. This property renders the SNEDDS into perfect drug delivery systems to deliver Biopharmaceutics Classification System Class II drugs with enhanced solubility. Materials and Methods: The SNEDDSs have different preparation methods, classified as high-energy method and low-energy methods. In low-energy method, phase inversion method or standard admixture method using vortex mixture was used to prepare formulations using various oils and surfactants. Results: Solubility of repaglinide was carried out in different vehicles; we observed that high solubility was found in neem oil (45 mg/mL), Cremophor RH 40 (21 mg/mL), Transcutol (48 mg/mL), and Span 80 (34 mg/mL). Ternary diagrams were drawn for oil:Smix ratios which were clear emulsion observed. From the phase diagrams, ratios possessing high oil percentage were considered, F1 to F7 formulation ratios were selected. All formulations were subjected to evaluation tests with no phase separation, no precipitation. F1 and F7 formulation has shown high in vitro drug release when compared with other formulations by forming nanosize particle 223 nm and 221nm, respectively. Conclusion: Repaglinide SNEDDSs have shown 157% increase in in vitro dissolution data when compared to marketed formulation.